lpha-2 Adrenergic and Opioids Receptors Participation in Mice Gastroprotection of Abelmoschus esculentus Lectin - A. Ribeiro, Kátia; V. Chaves, Hellíada; Mateus Pereira Filho, Samuel; Ribeiro Pinto, Isabela; Andressa Martins Monteiro, Dina; Oliveira Matos, Samuel; Santi-Gadelha, Tatiane; Alberto de Almeida Gadelha, Carlos; Thalles Jocelino Gomes de Lacerda, José; M. V. Aguiar, Lissiana; M. A. Pereira, Karuza; M. B. Benevides, Norma; et al. (Current Pharmaceutical Design, 2016)
Lectins are a heterogeneous group of proteins and glycoproteins with potential role as therapeutic and diagnostic tools to combat various diseases, besides some functions on human organism. Abelmoschus esculentus (Okra), a horticultural plant of African origin, is cultivated in northeastern Brazil, and used for different medicinal purposes. This work is aimed to elucidate the action mechanisms of Abelmoschus esculentus lectin (AEL) gastro protective effect on gastropathy induced by ethanol. Fasted mice treated with Ethanol 99.9% (0.2 ml/animal, p.o.) received previously AEL (0.01, 0.1, 1.0, 10 or 50 mg/kg, i.v.), saline (5 ml/kg; i.v.) or ranitidine (80 mg/kg, p.o.) in four experimental series, in which pharmacological tools (yohimbine, naloxone, L-NAME or indomethacin), were administered with the purpose of make clear possible molecular action mechanisms. Mice were euthanized 30 min after ethanol challenge to verify the stomach damages. Establishment of gastric oxidative stress, tissue hemoglobin (Hb) content and microscopic features (H) were taken in order to characterize the AEL gastro protective effect. AEL (1 mg/kg) was capable of protect mucosa against ethanol damages in presence of two (L-NAME and indomethacin) of four antagonists/inhibitors used. The AEL effect was reversed by naloxone and yohimbine, showing the involvement of opioids and lpha-2 adrenergic receptors on gastric protective effect of this lectin. Evaluation of microscopic features, oxidative stress, and Hb levels pointed the protective effects of AEL. This activity seems to be mediated by alpha-2 adrenergic and opioid receptors activation. Nitric oxide or prostaglandins were not involved. AEL simultaneously showed antioxidant effect that is probably implicated in its intricate defensive mechanism of action.
Keywords: Abelmoschus esculentus lectin